Drying Kinetics and Expansion of Non‐predried Extruded Starch‐Based Pellets during Microwave Vacuum Processing. Issue 6 (10th October 2013) - Kraus, Stefan; Sólyom, Katalin; Schuchmann, Heike P.; Gaukel, Volker
Abstract Drying kinetics of extruded, starch‐based pellets with initial moisture content of 0.695 kg/kg d.b. were experimentally investigated in a microwave vacuum drying system. The influence of the initial sample amount (100, 200 and 300 g), microwave power (400, 600 and 800 W) and system pressure (20, 50 and 100 mbar) were examined in detail. An increase in microwave power and a decrease in initial sample amount significantly shortened the drying time. Among several thin layer models, the model of Balbay and Sahin best describes the experimental data for starch‐based pellets. The activation energy was calculated to be 10.89 W/g and effective moisture diffusivity varied from 3.4 × 10−9 to 1.2 × 10−8 m2/s, depending on microwave power level and sample amount. Practical Application Third generation snacks provide an alternative to fully prepared puffed snack foods. In contrast to conventional extrusion, nonexpanded pellets are formed via extrusion, then predried and then expanded to achieve a crispy and porous texture. In this alternative process, the extrusion can be performed at high moisture content, moderate temperature and shearing conditions. This is beneficial for the preservation of thermally and mechanically sensitive ingredients and allows the production of snacks with high nutritional quality. A special feature of the process investigated in this study is that the expansion is achieved by microwave‐vacuum processing which allows an indirect expansion without a time‐ and energy‐consuming predrying process. In addition, due to the processing under vacuum, the temperature inside the product can be kept at desired moderate values. The drying kinetics, drying rate and diffusion coefficient in connection with the volume expansion allow process design and product quality improvement.